Mu Daiko: Drumming Between East and West - Ouyang, Lei X (MUSICultures)

(untitled) (Canadian Society for Traditional Music / La Société canadienne pour les traditions musicales, 2024)
This ethnographic study introduces Asian American taiko group Mu Daiko (now Ensō Daiko) through a look at three members and their original compositions. The group is well known for their emphasis on movement and theatricality and developed their own unique style in the American Midwest. This case study explores how Mu Daiko continues the tradition of Asian American taiko drumming while simultaneously innovating and pushing the art form in new directions. Furthermore, I examine how Mu Daiko operates within the larger North American taiko community, their social justice mission, and how the art form engages with, and is informed by, the larger Asian American movement.